Carcinogenic and non-carcinogenic risk for the population from the consumption of potatoes and vegetables growing within the limits of agro-residential landscapes - Myslyva, Tamara N.; Levshuk, Oksana N. (Journal of the Belarusian State University. Ecology, 2022)
One of the most effective methods of preventing the danger caused by the impact of carcinogenic and non-carcinogenic chemicals on humans is to establish the risk of undesirable effects in order to further development methods to minimize it. The purpose of this study is to establish the magnitude of the non-carcinogenic and carcinogenic risk caused by the intake of heavy metals when consuming potatoes and vegetables grown within the agro-residential landscapes of Gorki, as well as when contaminants enter the human body by the oral, inhalation and percutaneous route directly from the soil. It has been established that the maximum contribution to the exposure of Cu, Zn, Mn and Cd entering the body of the adult population of the city of Gorki is made by beetroot, potatoes and white cabbage. Table carrots and potatoes make the maximum contribution to the exposure of Cu and Cd for the child population, while the main sources of Zn, Mn, and Pb intake are potatoes and white cabbage. The total level of carcinogenic risk from the consumption of potatoes and vegetables due to such carcinogens as Pb and Cd is estimated as average according to the international criterion scale. The non-carcinogenic risk to the health of both adults and children due to inhalation, oral and percutaneous intake of heavy metals from contaminated soil is assessed as negligible, and the carcinogenic risk is at an acceptable level. The results of the studies performed can be used to develop a risk management strategy for the population due to pollution of urban soils, potatoes and vegetables with heavy metals, providing for the sequential passage of the following stages: comparative assessment and ranking of risk; determination of risk acceptability levels; risk reduction and control; response to risk.